STRATEGI KOMUNIKASI KEMITRAAN PO LAJU PRIMA DALAM MEMBERIKAN PELAYANAN MELALUI APLIKASI HIBA AKAP ONLINE - A.Irgi Wildan Syihab; Robbikal Muntaha Meliala; Teguh Tri Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the partnership communication strategy implemented by the Laju Prima Bus Company (PO) in delivering excellent service through the HIBA AKAP Online application. The research method used is descriptive qualitative, with data collected through observation, in-depth interviews, and documentation. The informants in this study included Laju Prima's management, ticket agent partners, and loyal customers. The findings reveal that Laju Prima's partnership communication strategy consists of five key components: (1) Shared agenda, (2) Common measurement system, (3) Mutually reinforcing activities, (4) Continuous communication, and (5) Strong supporting infrastructure. The HIBA AKAP Online application serves as a digital bridge that facilitates information transparency, operational efficiency, and reduces conflicts such as double booking. This study offers a new conceptual framework on integrating technology into business communication in the transportation sector.